Phosphasalen indium complexes showing high rates and isoselectivities in rac-lactide polymerisations - Myers, D; White, A; Forsyth, C; Bown, M; Williams, C (Wiley, 2017)
Polylactide (PLA) is the leading bioderived polymer, produced commercially by the metal catalysed ring-opening polymerisation of lactide. Control over tacticity to produce stereoblock PLA, from rac-lactide, improves thermal properties but is an outstanding challenge. Here, phosphasalen indium catalysts combine high rates (30 ± 3 M-1 min-1, THF, 298 K), high control, low loadings (0.2 mol%) and isoselectivity (Pi = 0.92, THF, 258 K). Furthermore, the phosphasalen indium catalysts do not feature any chiral additives.